DETERMINANT ISLAMIC SOCIAL REPORTING(ISR) IN COMPANIES REGISTERED IN JAKARTA ISLAMIC INDEX 70 (JJI 70): english - Mohamad Zulman Hakim; Dewi Rachmania; Hamdani Hamdani; Mikrad Mikrad; Siti Chanifah; Melsha Alfisa Wijaya (Cita konsultindo, 2022)
This study aims to obtain empirical evidence regarding the effect of company size, profitability, and leverage on Islamic social reporting (ISR). The population in this study uses the Jakarta Islamic Index 70 (JII 70) sector. Sampling technique using Purposive Sampling. Methods of data analysis using Panel Data Regression Analysis. The results of the study show that company size has a negative effect on Islamic Social Reporting (ISR). Profitability (ROA) has no effect on Islamic Social Reporting (ISR), Leverage (DER) has no effect on Islamic Social Reporting (ISR).